Mesozooplankton biomass and copepod estimated production in a temperate estuary (Mondego estuary): effects of processes operating at different timescales - Gonçalves, Dina Amanda (2015)
A fundamental step in characterizing marine planktonic communities is the knowledge of the variability of their biomass and production, in order to assess the flux of matter through the food web and estimate the fate of this energy. The zooplankton assemblage’s dynamics of the Mondego estuary (Portugal) have been extensively characterized, but none have focused on biomass and secondary production. In the present study, zooplankton biomass and secondary production were investigated with a seasonal basis in a fixed station, located at the mouth of the Mondego estuary (Portugal), with emphasis on the copepod community. In order to study the influence of physical processes operating at different temporal scales, sub-surface and near-bottom samples were collected every 2 h in diel and tidal cycles, over neap tides.